Targeting HER proteins in cancer therapy and the role of the non-target HER3 - Hsieh, A C (Nature Publishing Group, 2007)
Members of the human epidermal growth factor receptor (HER) family have been of considerable interest in the cancer arena due to their potential to induce tumorigenesis when their signalling functions are deregulated. The constitutive activation of these proteins is seen in a number of different common cancer subtypes, and in particular EGFR and HER2 have become highly pursued targets for anti-cancer drug development. Clinical studies in a number of different cancers known to be driven by EGFR or HER2 show mixed results, and further mechanistic understanding of drug sensitivity and resistance is needed to realise the full potential of this treatment modality. Signalling in trans is a key feature of HER family signalling, and the activation of the PI3K/Akt pathway, so critically important in tumorigenesis, is driven predominantly through phosphorylation in trans of the kinase inactive member HER3. An increasing body of evidence shows that HER3 plays a critical role in EGFR- and HER2-driven tumours. In particular, HER3 lies upstream of a critically important tumorigenic signalling pathway with extensive ability for feedback and cross-talk signalling, and targeting approaches that fail to account for this important trans-target of EGFR and HER2 can be undermined by its resiliency and resourcefulness. Since HER3 is kinase inactive, it is not a direct target of kinase inhibitors and not presently an easily drugable target. This review presents the current evidence highlighting the role of HER3 in tumorigenesis and its role in mediating resistance to inhibitors of EGFR and HER2.